2023
DOI: 10.1002/jmv.28864
|View full text |Cite
|
Sign up to set email alerts
|

Overview of autoantibodies in COVID‐19 convalescents

Abstract: Accumulating evidence shows that SARS‐CoV‐2 can potentially trigger autoimmune processes, which can be responsible for the long‐term consequences of COVID‐19. Therefore, this paper aims to review the autoantibodies reported in COVID‐19 convalescents. Six main groups were distinguished: (i) autoantibodies against components of the immune system, (ii) autoantibodies against components of the cardiovascular system, (iii) thyroid autoantibodies, (iv) autoantibodies specific for rheumatoid diseases, (v) antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 128 publications
2
8
0
1
Order By: Relevance
“…Previous studies showed an elevated rate of autoimmune and autoinflammatory diseases during the pandemic, increasing the rate of autoantibodies appearing in people infected with SARS‐CoV‐2 28–30 . Our findings align with these findings as observed by the significantly higher number of children positive for TTG antibodies during the pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed an elevated rate of autoimmune and autoinflammatory diseases during the pandemic, increasing the rate of autoantibodies appearing in people infected with SARS‐CoV‐2 28–30 . Our findings align with these findings as observed by the significantly higher number of children positive for TTG antibodies during the pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…In severe COVID-19, Tph cells and DN2 B cells also increase in the peripheral blood, and SHM is low in DN2 B cells ( 23 , 51 ). Upregulation of autoantibodies such as anti-nuclear antibody and ACPA in COVID-19 patients supports the physiological significance of Tph and DN2 cells in COVID-19 patients ( 52 ).…”
Section: B-cell Helper Activity Of Tph Cellsmentioning
confidence: 57%
“…При адаптации классических серологических подходов, включающих метод непрямой иммунофлюоресценции (НИФ) и иммуноферментный метод (ИФМ) с «омиксными» технологиями (белковые микрочипы, мультиплексный анализ, библиотека пептидов, фаговый дисплей, проточная цитофлюориметрия, масс-спектрометрия и др. ), определяющихся как «аутоантигеномика» [112], в сыворотках пациентов с COVID-19 обнаружен широкий спектр органоспецифических и органонеспецифических аутоантител, некоторые из которых «уникальны» для COVID-19, другие встречаются при различных аутоиммунных заболеваниях [7][8][9][10][11][113][114][115][116]. Аутоантитела, выявляемые в сыворотках пациентов, инфицированных SARS-CoV-2, в различные периоды болезни, можно условно разделить на следующие основные категории:…”
Section: аутоантителаunclassified